2003
DOI: 10.1021/jf0259213
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Conjugated Linoleic Acids in Soybean Oil during Hydrogenation with a Nickel Catalyst As Affected by Sulfur Addition

Abstract: The effects of sulfur addition on the formation of conjugated linoleic acid (CLA) isomers were studied during the hydrogenation of soybean oil with a nonselective type nickel catalyst. Sulfur addition greatly promoted CLA formation in soybean oil during hydrogenation. As the amount of sulfur increased to a certain level, the maximal quantity of CLA in soybean oil during hydrogenation increased greatly. However, further increase in sulfur addition above the certain level decreased CLA formation. The optimal sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…It is well‐known that during the hydrogenation process of vegetable oils, sulfur reduces the catalyst activity and induces the isomerization of cis monoenoic fatty acids to their trans ‐C18:1 isomers 30. All our results were consistent with those previously reported by Ju and Jung, who used a nonselective nickel catalyst 16…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It is well‐known that during the hydrogenation process of vegetable oils, sulfur reduces the catalyst activity and induces the isomerization of cis monoenoic fatty acids to their trans ‐C18:1 isomers 30. All our results were consistent with those previously reported by Ju and Jung, who used a nonselective nickel catalyst 16…”
Section: Resultssupporting
confidence: 93%
“…These authors concluded that selective hydrogenation could be more favorable than nonselective hydrogenation, yielding predominantly trans – trans CLA isomers. In view of those results, Ju and Jung reported that sulfur‐poisoning effect in selective nickel catalyst (SP‐7 Engelhard) might be responsible of the promotion of CLAs formation during hydrogenation without giving any scientific justification 16…”
Section: Introductionmentioning
confidence: 99%
“…[RhCl(C 8 H 14 ) 2 ] 2 can be used as homogeneous catalyst for the isomerization of vegetable oils [26]. Heterogeneous catalysts contain common hydrogenation metals, e.g., ruthenium [27], nickel [28], rhodium [29], and iridium [30], although the low CLA yield still prevents their industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…Since the health benefits of trans,trans-CLA are emerging, there is an increasing realization of the value of an oil with more trans,trans-CLA than is currently possible with photo-isomerized soy oil. Ju and Jung [15] showed that soy oil hydrogenation could be manipulated to produce 12 % trans,trans-CLA by adding sulfur with nickel as a catalyst; however, this process was accompanied with the formation of 19 % elaidic acid which is undesirable in food-grade oil [15]. trans,trans-CLA FAME were produced from synthetic CLA free fatty acids using BF 3methanol catalyzed methylation [16]; however, this method was unable to directly produce trans,trans-CLA TAG and the process is laborious and time consuming taking over 24 h to complete.…”
Section: Introductionmentioning
confidence: 99%